Diseño de planta para la optimización y mejoramiento productivo de la empresa Kingspan Group (2023)
This study examines the challenges that a company faces in the organization of its production plant, specifically in relation to machinery, raw materials and the storage of finished products. These challenges arose due to a significant increase in sales in a short period of time, with a distribution area that went from 40,000 to 100,000 square meters. It was determined that the current design of the plant was not optimal and could not meet the current needs of the company. In addition, the acceleration in production and the increased level of storage of materials and finished products have required major changes in the plant. As a consequence, there has also been a notable increase in the number of non-compliant panels that require recycling. This study will collect data on the current layout of the plant, the production flow, the storage of raw materials and finished products, as well as the recycling process for non- conforming panels. Analytical tools and recognized methodologies will be used to identify problem areas and propose suitable solutions that optimize the organization of the plant and improve the efficiency of production and distribution. The results of this study are expected to provide the company with a clear understanding of the challenges it faces in terms of plant organization and layout, and offer practical recommendations to overcome these issues. The implementation of the proposed solutions will allow the company to achieve an optimal level of efficiency in its processes, maximize the use of resources and guarantee the satisfaction of the current and future needs of the company.